Exploring the influence of trauma on ethical theory understanding: a narrative literature review based on public administration education - Nhari, Sibongile Ruth; Taka, Charlotte; Nzimakwe, Thokozani Ian (Frontiers in Education, 2025)
This paper explores the intersection of trauma, ethics, and public administration pedagogy, focusing on the impact of intergenerational trauma on students’ comprehension and application of ethical theories in post-colonial contexts such as South Africa. The aim of the study is to critically examine how traditional Western ethical frameworks, such as deontology, utilitarianism, and virtue ethics, align—or fail to align—with the lived experiences of students affected by historical trauma, and to explore the development of context-specific ethical frameworks rooted in African philosophical thought. The study employs a critical narrative review methodology, synthesizing recent literature on trauma, ethics education, and decolonising pedagogy to identify key challenges and gaps in existing research. The analysis reveals that traditional ethical frameworks often fail to address the cognitive and emotional barriers faced by students from marginalised communities, whose historical and collective trauma impedes their engagement with abstract ethical theories. In particular, the findings highlight a critical gap in trauma-informed pedagogical strategies, which are essential for fostering a deeper understanding of ethics in public administration. The paper concludes that contextually constructed ethical frameworks, particularly those informed by African philosophical traditions like Ubuntu, offer a more relevant and effective approach to ethics education in post-apartheid South Africa. The study recommends the integration of trauma-sensitive, context-specific pedagogical strategies to enhance the ethical decision-making capacities of public administration students. Additionally, it calls for the use of technological and pedagogical innovations, such as virtual simulations and interdisciplinary approaches, to advance the teaching of ethics to trauma-affected populations. These recommendations aim to prepare future public servants for the complex ethical challenges they will encounter in governance and public service, particularly in societies shaped by historical trauma.